Empowerment of Adolescent Girls in Managing Menstrual Disorders through Communication-Based Complementary Therapy in Sangkanwangi Village, Leuwidamar District, Lebak Regency - Afrilia, Eka Mardiana; Ajeng, Atnesia; Kristian, Agus (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Menstrual disorders in the form of dysmenorrhea are among the most common reproductive health problems experienced by adolescent girls and have an impact on learning activities, psychological well-being, and overall quality of life. Limited understanding, lack of open communication, and restricted access to youth-friendly health information are barriers to appropriate dysmenorrhea management. This community service program aimed to empower adolescent girls in managing menstrual disorders through complementary therapy based on therapeutic communication. The implementation method applied a community empowerment approach, with therapeutic communication as the primary method, consisting of the pre-interaction, orientation, working, and termination phases. Interventions were delivered through dialogic education, individual counseling, group education sessions, and guided practice of complementary therapies, including warm compresses and acupressure. Therapeutic communication techniques included empathy, active listening, emotional validation, reflection of feelings, clarification, and positive reinforcement. Educational leaflets were used to strengthen health messages. The results demonstrated the establishment of a therapeutic relationship between midwifery professional students and adolescent girls, increased feelings of safety and trust, improved understanding of dysmenorrhea, and enhanced ability among adolescents to independently practice warm compress and acupressure therapies.